Bortezomib maintenance after R‐CHOP, cytarabine and autologous stem cell transplantation in newly diagnosed patients with mantle cell lymphoma, results of a randomised phase II HOVON trial. (9th March 2020) - Doorduijn, Jeanette K.; Zijlstra, Josee M.; Lugtenburg, Pieternella J.; Kersten, Marie Josee; Böhmer, Lara H.; Minnema, Monique C.; MacKenzie, Marius A.; van Marwijk Kooij, Rien; de Jongh, Eva; Snijders, Tjeerd J.F.; de Weerdt, Okke; van Gelder, Michel; et al.
Abstract: Rituximab‐containing induction followed by autologous stem cell transplantation (ASCT) is the standard first‐line treatment for young mantle cell lymphoma patients. However, most patients relapse after ASCT. We investigated in a randomised phase II study the outcome of a chemo‐immuno regimen and ASCT with or without maintenance therapy with bortezomib. Induction consisted of three cycles R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone), two cycles high‐dose cytarabine, BEAM (carmustine, etoposide, cytarabine, melphalan) and ASCT. Patients responding were randomised between bortezomib maintenance (1·3 mg/m 2 intravenously once every 2 weeks, for 2 years) and observation. Of 135 eligible patients, 115 (85%) proceeded to ASCT, 60 (44%) were randomised. With a median follow‐up of 77·5 months for patients still alive, 5‐year event‐free survival (EFS) was 51% (95% CI 42–59%); 5‐year overall survival (OS) was 73% (95% CI 65–80%). The median follow‐up of randomised patients still alive was 71·5 months. Patients with bortezomib maintenance had a 5‐year EFS of 63% (95% CI 44–78%) and 5‐year OS of 90% (95% CI 72–97%). The patients randomised to observation had 5‐year PFS of 60% (95% CI, 40–75%) and OS of 90% (95% CI 72–97%). In conclusion, in this phase II study we found no indication of a positive effect of bortezomib maintenance after ASCT.